Strategi Penurunan Pencemaran Perairan Akibat Limbah Pabrik dengan Pembuatan Resirkulasi Air Sistem Biofilter Anaerob-Aerob di Desa Burai, Sumatera Selatan - Salman Huda; Ainun Mardhiyyah; Ismawati Oktavia; Regita Umami; Faddilla Amalia; Mirna Fitrani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Huda S, Mardhiyyah A, Oktavia I, Umami R, Amalia F, Fitrani M. 2021. Strategy for reducing water pollution due to plant waste by making water recirculation anaerobic-aerobic biofilter system in burai village, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 338- 347 Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Waste is a problem that a national and international scale has discussed. Those domestic and industrial waste harms the waters. One of them occurs in the waters of Burai Village, Ogan Ilir Regency, South Sumatra, which has a plant waste problem in the form of liquid waste flowing along the river and can reduce water quality in the area. The research shows that the river in Burai village does not meet the cultivation requirements because heavy metals contaminate it with high hardness and total coliform, which is not suitable for drinking water. The purpose of this study was to reduce the pollution of river waters and support the aquaculture process. The writing method in this study using the literature study method. The study results show that water recirculation with a biofilter system can reduce water quality degradation by the filtration process and control dissolved solids that the cultivation system can adapt. The biofilter system used is an anaerobic-aerobic immersed biofilter system. Water recirculation with this system is proven to be able to control the total ammonia nitrogen and nitrite. Therefore, water recirculation can be applied to maintain water quality to support the cultivation business in the village.